2016
DOI: 10.1177/0004867416652736
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines in major depressive disorder: A case–control study

Abstract: Introduction: There is mixed evidence in the literature on the role of inflammation in major depressive disorder. Contradictory findings are attributed to lack of rigorous characterization of study subjects, to the presence of concomitant medical illnesses, to the small sample sizes, and to the limited number of cytokines tested.Methods: Subjects aged 18-70 years, diagnosed with major depressive disorder and presenting with chronic course of illness, as well as matched controls (n = 236), were evaluated by tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 42 publications
7
35
1
Order By: Relevance
“…In particular, while depressive symptoms correlate with several adverse outcomes, 33 it has been observed that depressive symptoms are also present in the nonclinical general population. 34 Moreover, while in MDD, some studies do not confirm the inflammatory theory of depression, 35 others strongly suggest a subpopulation that could benefit from treatment with antiinflammatory drugs. 36 Hence, our data cannot preclude the possibility that aspirin is beneficial in a subpopulation of individuals with MDD.…”
Section: Figurementioning
confidence: 99%
“…In particular, while depressive symptoms correlate with several adverse outcomes, 33 it has been observed that depressive symptoms are also present in the nonclinical general population. 34 Moreover, while in MDD, some studies do not confirm the inflammatory theory of depression, 35 others strongly suggest a subpopulation that could benefit from treatment with antiinflammatory drugs. 36 Hence, our data cannot preclude the possibility that aspirin is beneficial in a subpopulation of individuals with MDD.…”
Section: Figurementioning
confidence: 99%
“…Nevertheless, Hypiran decreased the levels of IL-6 more profoundly than Prednisolone. Interestingly, it is clear that patients with depression disorders show increased levels of proinflammatory cytokines like IL-6 and H. perforatum extract may have beneficial effects in the treatment of depression via decreasing the levels of IL-6 and altering the neuromediators [10,40].…”
Section: Gross Appearance Of the Colonic Mucosa In Experimental Groupsmentioning
confidence: 99%
“…Therefore, regulatory T cells or myeloid‐derived suppressor cells should be included in future studies to adjust for global elevations in cytokines due to tumor. Lastly, a recent study on cytokine levels of patients with MDD and chronic illness (compared with those of matched controls) found that there is no significant association between measures of systemic inflammation . The authors of the study hypothesized that MDD can be induced by comorbid inflammatory processes mediated by elevated serum cytokines .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a recent study on cytokine levels of patients with MDD and chronic illness (compared with those of matched controls) found that there is no significant association between measures of systemic inflammation. 38 The authors of the study hypothesized that MDD can be induced by comorbid inflammatory processes mediated by elevated serum cytokines. 38 Future studies should recruit otherwise healthy MDD patients as matched controls to study the change of inflammatory cytokines in depressed cancer patients.…”
Section: Times As Many Female Patients With Hcc Demonstrated Clinicallymentioning
confidence: 99%
See 1 more Smart Citation